ARABIC LINGUISTICS IN HISTORICAL AND ISLAMIC CULTURE PERSPECTIVES - Bachmid, Gayda (Center for Research and Development of Religious Literature and Heritage, 2016)
This writing has the Arabic linguistic phenomena cherished by its users though withÂ limited competence as its background. The research aim is to describe the determining factors why the Arabic language is accepted and cherished by the Muslim community in Manado. Primary data source is the selected respondents in line with the religious social group representative category. The secondary data originate from bibliography. The research findings indicate there are two main factors determining the Arabic language to be idolized by the user community, i.e culture and history. Cultural study results in values, thinking pattern, conviction, admiration, sacredness, and the beauty of literary art, the richness of vocabulary implicating virtues. The historical context narrates that the Arabic linguistics is the language of prophecy, the language that shifted the ancient civilization to modern era, the translating language of science and technology as a validity spirit transformation mover of the western world revival.Key words:Â Arabic linguistics, culture and history.Â Tulisan ini dilatarbelakangi oleh fenomena linguistik Arab yang digandrungi oleh para pengguna walaupun dalam kompetensi yang terbatas. Tujuan penelitian ini adalah mendeskripsikan faktor determinan bahasa Arab diterima dan diagungkan oleh masyarakat Muslim di Manado. Sumber data primer dari responden yang dipilih sesuai dengan kategori perwakilan kelompok sosial keagamaan. Data sekunder bersumber pada sejumlah pustaka. Hasil penelitian ini menunjukkan bahwa ada 2 faktor utama menjadi penentu masyarakat pengguna menjunjung tinggi linguistik Arab yaitu budaya dan sejarah. Kajian budaya ditemukan nilai-nilai, pola pikir, keyakinan, kekaguman, kesakralan, keindahan seni sastra dan kekayaan kosa kata yang berimplikasi kebajikan. Konteks sejarah menarasikan bahasa linguistik Arab adalah bahasa kenabian, bahasa yang menggeserkan peradaban kuno ke era modernitas, bahasa penerjemah sains dan teknologi sebagai transformasi ruh validitas penggerak kebangkitan dunia barat.Kata kunci: linguistik Arab, budaya dan sejarah.